AgBr-Coupled TiO2: A Visible Heterostructured Photocatalyst for Degrading Dye Pollutants - Jianjun Liu; Yingchun Yu; Zhixin Liu; Shengli Zuo; Baoshan Li (International Journal of Photoenergy)
A series of AgBr/TiO2 visible photocatalysts with heterojunction structure was synthesized using Ti(OC4H9)4, KBr, and AgNO3 as precursors. The phase composition, particle morphology and size, microstructures, and absorbance of these photocatalysts were characterized by X-ray diffraction, transmission electron microscope (TEM), high-resolution TEM, and UV-vis spectra. It was found that the coupled AgBr/TiO2 was an effective photocatalyst to degrade the methylene blue under visible light irradiation, compared with the other noncoupled photocatalysts of AgBr, AgBr/P25, and P25. The photocatalytic activities of AgBr/TiO2 increase first and then decrease with increasing the mass ratio of mAgNO3/mTiO2 and the photocatalyst with the mass ratio of 3.35 has the highest photocatalytic activity. The results showed that the coupled photocatalyst has the particle size of about 15 nm with homogeneous dispersion and has the strongest absorption in whole UV-vis light region (250∼800 nm) originated from the synergetic effect of heterostructured AgBr/TiO2. The coupled AgBr/TiO2 photocatalyst can keep stable photocatalytic activity after five-circle runs.